A Survey of Counseling Curricula Among Accredited Communication Sciences and Disorders Graduate Student Programs. - Doud, Aspen K.; Hoepner, Jerry K.; Holland, Audrey L. (American Journal of Speech-Language Pathology, 2020)
Purpose: The purpose of this article is to examine the current state of counseling curriculum within the discipline. The last systematic survey of counseling curriculum within the disciplines of communication sciences and disorders was completed with data from 1983 (McCarthy et al., 1986). The Council on Academic Accreditation in Audiology and Speech-Language Pathology (2017) states that counseling should be included in accredited programs but does not specify to what extent. Currently, there are no standards to specify number of credits, need for a stand-alone course, or guidance regarding content delivered. Method: The present investigation collected data on the status of counseling curricula in accredited communication sciences and disorders graduate programs. A Qualtrics survey was distributed to identify counseling curriculum practices across accredited programs. Quantitative data such as percentages and frequency counts were compiled to summarize program offerings. Qualitative analyses were used to characterize written responses. Survey responses were also cross-validated with a review of offerings listed on program websites. Results: Of programs currently accredited by the Council on Academic Accreditation in Audiology and Speech-Language Pathology, 42.4% responded to the current survey. Fifty-nine percent of programs offer a stand-alone course. Review of curricula from program websites indicated that only 40% of accredited programs offer a stand-alone counseling course. Quantitative details about requirements, number of credits, and embedding counseling within other courses were compared to data from the 1983 survey. Qualitative analyses identified common learner outcomes and the nature of course or curricular content. Conclusions: Investigators found a lack of consistency in incorporating counseling across programs and discussed implications of this in speech-language pathology practice. A decrease in the number of programs that offer a standalone counseling course was identified as compared to offerings in 1983, as well as a disparity regarding how programs provide training in counseling. Furthermore, survey responses differed from curriculum listings on program websites. Information derived from this study may serve as a starting point for the development of flexible standards that provide direction for achieving consistent preparation of counseling skills.